IMMUNOHISTOCHEMICAL EXPRESSION OF HUMAN EPIDERMAL GROWTH FACTOR RECEPTOR-2 (HER-2) IN COMMON SALIVARY GLAND CARCINOMAS - Saeed, Zunaira; Zafar, Nadeem; Ara, Nighat; Muneer, Saadia; Asif, Zainab; Haroon, Azka; Saeed, Zahra (Journal of Ayub Medical College Abbottabad, 2023)
Background: Carcinomas of the salivary gland are known to be aggressive in nature, making them difficult to manage. The therapeutic options offered include excision of the gland (maxillectomy in cases of palatal tumours), with or without lymph node dissection, proceeded with radiotherapy. Chemotherapy has not produced promising outcomes and has a minimal impact as a therapeutic alternative. Targeted therapy against human epidermal growth factor receptor 2 (HER-2), which is a commonly used treatment modality for their mammary analogues, is not being offered to these patients since scant literature is available showing its usefulness and no promising evidence is present regarding their efficacy and efficiency in such cases. The study aimed to evaluate and quantify the immunohistochemical expression of HER-2 in cases of adenoid cystic carcinoma (AdCC), mucoepidermoid carcinoma (MEC) and salivary duct carcinoma (SDC), which are analogues of similar tumours arising in breast tissue. Methods: A retrospective, cross-sectional study was carried out in the department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, duration of which was six months. A total of 45 cases (15 of each tumour) were taken, and sampled using non-probability convenience technique. The immunohistochemical marker, monoclonal HER-2 antibody (Leica microsystem Germany) was applied on appropriate blocks of all included cases. The staining pattern and intensity were recorded after visualizing the slides under a light microscope. Results: Seven cases of salivary duct carcinoma and a single case of mucoepidermoid carcinoma expressed positivity for HER-2, while no expression could be seen in the case of adenoid cystic carcinoma. A statistically significant difference was seen when HER-2 expression was compared among the aforementioned tumours. Conclusion: The use of targeted therapy against HER-2 is limited to patients of salivary duct carcinoma and a fraction of patients suffering from mucoepidermoid carcinoma.